THROMBOCYTOPENIA AMONG NEONATES HAVING CULTUREPROVEN SEPSIS AT A TERTIARY CARE HOSPITAL IN PAKISTAN - Zehravi, Syeda Shamama; Khan, Mashal; Sheikh, Mehmood; Mohammad Hanif; Wajid, Sumaira (Journal of Postgraduate Medical Institute, 2022)
Objectives: To determine the frequency of thrombocytopenia in culture-positive neonatal sepsis. Methodology: This hospital-based cross-sectional study was conducted at a tertiary care hospital of Pakistan between July to December 2021 at the Department of Pediatrics, National Institue of Child Health Karachi - Pakistan. All the neonates admitted to NICU with signs and symptoms of sepsis and positive blood culture were enrolled for this study. Complete blood count, C - reactive protein (CRP) and blood culture were sent. All the data regarding age, gender, birth weight, platelet count, and the organism isolated on blood culture was recorded in a proforma. Data was analyzed statistically and p=0.05 was considered to be statistically significant. Results: Two hundred forty-six babies were included in the study. The mean gestational age was 37±0.56 weeks and birth weight was 3.4±0.67 kg. Male to female ratio was 1.2:1 and the mean age of admission was 6.37+5.99 days. Thrombocytopenia was found in 192 (78.4%) of neonates. There was a significant association of Burkrolderia cepacia (p=0.002), Klebsiella pneumonia (p=0.032), and Serratia marcescens (p=0.027) with thrombocytopenia. Conclusions: Thrombocytopenia is strongly associated with gram-negative bacteria and the most prevalent organism found in thrombocytopenic neonates was Burkrolderia cepacia.